Diving Into Reef Ecosystems for Land-Agriculture Solutions: Coral Microbiota Can Alleviate Salt Stress During Germination and Photosynthesis in Terrestrial Plants - Ocampo-Alvarez, Héctor; Meza-Canales, Iván D.; Mateos-Salmón, Carolina; Rios-Jara, Eduardo; Rodríguez-Zaragoza, Fabián A.; Robles-Murguía, Celia; Muñoz-Urias, Alejandro; Hernández-Herrera, Rosalba Mireya; Choix-Ley, Francisco Javier; Becerril-Espinosa, Amayaly (Frontiers in Plant Science, 2020)
From their chemical nature to their ecological interactions, coral reef ecosystems have a lot in common with highly productive terrestrial ecosystems. While plants are responsible for primary production in the terrestrial sphere, the photosynthetic endosymbionts of corals are the key producers in reef communities. As in plants, coral microbiota have been suggested to stimulate the growth and physiological performance of the photosynthetic endosymbionts that provide energy sources to the coral. Among them, actinobacteria are some of the most probable candidates. To explore the potential of coral actinobacteria as plant biostimulants, we have analyzed the activity of Salinispora strains isolated from the corals Porites lobata and Porites panamensis, which were identified as Salinispora arenicola by 16S rRNA sequencing. We evaluated the effects of this microorganism on the germination, plant growth, and photosynthetic response of wild tobacco (Nicotiana attenuata) under a saline regime. We identified protective activity of this actinobacteria on seed germination and photosynthetic performance under natural light conditions. Further insights into the possible mechanism showed an endophytic-like symbiosis between N. attenuata roots and S. arenicola and 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity by S. arenicola. We discuss these findings in the context of relevant ecological and physiological responses and biotechnological potential. Overall, our results will contribute to the development of novel biotechnologies to cope with plant growth under saline stress. Our study highlights the importance of understanding marine ecological interactions for the development of novel, strategic, and sustainable agricultural solutions.